A Genre-Based Analysis of Vietnam Tourist Attraction Brochures with Pedagogical Purposes - Nguyen, Thi Dung; Modehiran, Prannapha (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
Tourism brochure is one of the most popular advertising channels in the tourism industry and an inevitable task of tourism staff’s work. In learning and teaching English for tourism, tourism brochures can be used as teaching materials and a way of exposing students to authentic texts. In the new technology era, digital brochures play a vital role in tourism promotion. Therefore, this study aimed to explore digital attraction brochures’ generic structure for contributing to brochure writing and implications in English for tourism. In this research, 24 digital Vietnamese attraction brochures of highly reputed company websites in Vietnam were selected by purposive sampling for analysis based on Bhatia’s (2004) move-structural analysis. The findings were figured out with the generic structural model of the brochures, which comprised six moves, including (1) Captivating Titles, (2) Targeting Potential Tourists, (3) Attractions Information, (4) Establishing Credentials, (5) Directive Information, and (6) Soliciting Responses. The strategies for designing tourism brochures included four communicative purposes: attention getting, information supplying, persuasive messaging, and reaction reminding. Through the research findings, pedagogical implications were finally recommended as an English for tourism instruction.